Ankle Injuries in Dancers. Issue 16 (15th August 2019) - Vosseller, J. Turner; Dennis, Elizabeth R.; Bronner, Shaw
Abstract : The term dance encompasses a broad range of different styles; much of the orthopaedic literature has focused on ballet dancers. Injury is common in dancers at all levels, and many serious dancers sustain multiple injuries as they progress through their career. Foot and ankle injuries are among the most common injuries experienced by dancers. These injuries include those that are specific to dancers because of the unique physical maneuvers required to effectively perform, but they can also include common injuries that may require relatively different treatment because of the physical demands of the dancer. Os trigonum syndrome and flexor hallucis longus tenosynovitis generally fall into the former category as they are injuries that are more prevalent in dancers due to the extreme plantarflexion involved in dancing, especially ballet, and the relative demand placed on the toe flexors, most notably the flexor hallucis longus. On the other hand, anterior ankle impingement occurs both in dancers and in the general public. In many cases, a team approach to treatment with knowledgeable physical therapists can obviate the need for surgical treatment. If surgical treatment proves necessary, good results can be achieved with sound surgical technique and a well thought-out rehabilitation program.